Association between chest CT features and spirometry findings of patients with bronchiectasis (Journal of Chitwan Medical College, 2026)
Introduction: Bronchiectasis is characterized by irreversible bronchial dilatation and leads to diverse pulmonary function impairment. While high-resolution computed tomography (HRCT) is the gold standard for structural diagnosis, spirometry assesses functional status. Data on the correlation between specific CT features and spirometry patterns locally are limited.Methods: A cross-sectional observational study was conducted at Chitwan Medical College, Nepal, over two months in 2023 using convenience sampling following ethical approval. Stable adult patients (>18 years) with HRCT-confirmed bronchiectasis were included. HRCT patterns (cylindrical, varicose, cystic, or fibrobronchiectasis) were compared for association with spirometry pattern (normal, obstructive, restrictive, or mixed) based on post-bronchodilator values. Chi-square test was used for association using IBM SPSS Statistics with 95% confidence interval (CI), and p